2022
DOI: 10.3390/antiox11081534
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasma Membrane NADPH Oxidase in Response to Salt Stress in Cucumber Seedlings

Abstract: Plasma membrane NADPH oxidases (RBOHs, EC 1.6.3.1) are known as the main ROS generators involved in plant adaptation to stress conditions. In the present work, regulation of NADPH oxidase was analyzed in cucumber (Cucumis sativus L. var. Krak) seedlings exposed to salinity. RBOH activity and gene expression, as well as H2O2 content, were determined in the roots of plants treated with 50 or 100 mM NaCl for 1 h, and 50 mM NaCl for 1 or 6 days. It was found that enzyme activity increased in parallel with an enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…In cucumber plants grown on NUGE, we observed increased H 2 O 2 levels, lipid peroxidation, APX activity, and proline content in the shoots ( Figure 5 ). The reaction of plants to salinity is often accompanied by increased production of H 2 O 2 [ 24 , 30 , 68 , 69 ]. NUGE-cultivated plants accumulated much more H 2 O 2 than the plants nourished with RCF ( Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In cucumber plants grown on NUGE, we observed increased H 2 O 2 levels, lipid peroxidation, APX activity, and proline content in the shoots ( Figure 5 ). The reaction of plants to salinity is often accompanied by increased production of H 2 O 2 [ 24 , 30 , 68 , 69 ]. NUGE-cultivated plants accumulated much more H 2 O 2 than the plants nourished with RCF ( Figure 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…APX activity was slightly stimulated in cucumbers grown on NUGE ( Figure 5 D), whereas CAT activity did not change. Stimulation of both APX and CAT in response to NaCl has been reported in many plant species [ 30 , 76 ]. However, a greater increase in CAT activity was observed in salt-tolerant plants but not in salt-sensitive plants [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RBOH is a key producer of ROS in plants, and the specific regulation of RBOH expression plays an important role in plant resistance to stress [ 30 , 31 , 32 ]. Kabała et al reported that CsRBOHD and CsRBOHF1 expression are induced at the early stages of salt stress in cucumber seedlings, and H 2 O 2 is generated, which functions as a signaling molecule participating in the stress response [ 33 ]. This is consistent with the findings of Gémes et al in tobacco [ 34 ].…”
Section: Ros Metabolism Under Abiotic Stressmentioning
confidence: 99%